A self-consistent model of rate-dependent plasticity of polycrystals - Kiryk, R.; Petryk, H. (Archives of Mechanics, 1998)
The Hill-Hutchinson self-consistent scheme for polycrystals is extended to rate-dependent plasticity with work-hardening. A computational version of the model requires three material parameters for a single crystal which are approximately identified from the experimental stress-plastic strain curve for a polycrystalline material. Contours of the macroscopic plastic potential are calculated after different plastic prestrains in uniaxial tension.